Growing Apart: Religious Reflection on the Rise of Economic Inequality - Kate Ward; Kenneth R. Himes (MDPI, 2019)
Many people are increasingly concerned about economic inequality within their own nations, or between wealthy nations and poor ones. But is today's vast economic inequality best addressed by appeals to ethics, by altering social structures such as taxes and laws, or some combination of the two approaches? This volume brings together leading scholars from across the disciplines who believe today's extreme economic inequality threatens human flourishing and who are determined to address it using their own disciplinary tools. The broadly interdisciplinary volume incorporates contributions from fields as varied as theology, philosophy, economics, education, social work, sociology and law. Our work together illustrates how incorporating a variety of perspectives in a conversation enriches religious and ethical reflection on a significant social ill, and how quantitative and secular fields can help offer practical solutions to contemporary ethical problems.
Keywords: 330